1989
DOI: 10.1139/f89-148
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Lipid as a Factor Modulating Xenobiotic Metabolism in Channel Catfish (Ictalurus punctatus)

Abstract: Adult channel catfish (Ictalurus punctatus) were fed diets containing menhaden oil (MHO), soybean oil (SBO), or beef tallow (BFT) as lipid sources for 116 d. The effects of these diets on two important hepatic xenobiotic-metabolizing enzyme systems, cytochrome P-450-dependent monooxygenases (MOs) and glutathione S-transferases (GSTs), were evaluated. Microsomal MO and cytosolic GST activities were consistently greater in fish fed MHO than in those receiving SBO or BFT. Generally, enzyme activities in fish fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

1990
1990
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 9 publications
1
9
1
Order By: Relevance
“…Although no effects of dietary nutrient content or ration size were observed in this study, other studies have demonstrated that both dietary nutrient content and dietary quantity may have significant effects on an animal's stress response (Barton et al, 1988;Farbridge and Leatherland, 1992) and on detoxification ability (Ankley et al, 1989, Vigano et al, 1993Blom et al, 2000). However, results of these studies have provided equivocal results to the degree of the effects and demonstrated that more research is needed in this area.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Although no effects of dietary nutrient content or ration size were observed in this study, other studies have demonstrated that both dietary nutrient content and dietary quantity may have significant effects on an animal's stress response (Barton et al, 1988;Farbridge and Leatherland, 1992) and on detoxification ability (Ankley et al, 1989, Vigano et al, 1993Blom et al, 2000). However, results of these studies have provided equivocal results to the degree of the effects and demonstrated that more research is needed in this area.…”
Section: Discussioncontrasting
confidence: 77%
“…Increasing the lipid concentration (0.4, 7, 14, 21%) of diets fed to juvenile red drum (Sciaenops ocellatus) resulted in a significant (3-fold) increase in hepatic EROD activity between the diets with the lowest and highest lipid content (Craig et al, 1999). Moreover, varying the nature of the lipid, polyunsaturated v. saturated and type of fatty acid, has been shown to variably increase basal EROD and GST activities in the channel catfish (Ictalurus punctatus) (Ankley et al, 1989). Therefore, dietary content can affect detoxification enzyme activity in fish, although the extent of the relationship remains unclear.…”
Section: Biotransformation Systemmentioning
confidence: 99%
“…In the case of the PAHs and PCBs used as indicators in this study, uptake via food can be important. Differences in diets during the second and third year of the experiment may therefore have resulted in variation in the uptake of these pollutants and also, via an altered dietary lipid content, may have led to altered metabolism (27) and bioavailability of the same pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the development of vaccines, antibiotics usage in EU aquaculture has decreased markedly in the past decade, as shown by monitoring studies (European Commission 2002). Even though residues are kept under control for consumer safety, they may still be able to interfere with physiologic and/or metabolic processes of farmed fish and compromise their ability to metabolize other drugs and likely toxic chemicals (Ankley et al 1989;Vaccaro et al 2003). …”
Section: Food Safety: Animal Welfare and Human Consumptionmentioning
confidence: 99%